2020
DOI: 10.3390/app10207047
|View full text |Cite
|
Sign up to set email alerts
|

Drill Hole Orientation: Its Role and Importance on the Compression Response of Pure Magnesium

Abstract: Drilling is used in creating cylindrical through-holes for various applications. While optimizing drilling parameters is widespread, the effect of a drilled through-hole on the structural stability of components is not fully documented. The base material, along with other parameters, such as drill diameter, drill location and its orientation affect structural stability. Since carrying out tests on different base materials can be time consuming, simulation software can instead be used to provide valuable inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, table 2 concluded that for a drill depth of 1.5 mm, 1 mm and 1.5 mm drill diameters provided the best results. Further, previous studies [15,16] also emphasized on the better performance of the 1.5 mm vertical drill hole. Hence, with a 1.5 mm drill hole diameter and 1.5 mm drill depth, a study was conducted on square shaped holes as well as a hexagon shaped holes as shown in figure 3.…”
Section: Simulation Results and Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In addition, table 2 concluded that for a drill depth of 1.5 mm, 1 mm and 1.5 mm drill diameters provided the best results. Further, previous studies [15,16] also emphasized on the better performance of the 1.5 mm vertical drill hole. Hence, with a 1.5 mm drill hole diameter and 1.5 mm drill depth, a study was conducted on square shaped holes as well as a hexagon shaped holes as shown in figure 3.…”
Section: Simulation Results and Discussionmentioning
confidence: 96%
“…Five samples per orientation were tested to arrive at the stress-strain behaviour. The results of this study were compared with previous studies [15,16] where samples with no drill and through hole drills were done. All manufacturing parameters, compression testing parameters were kept consistent with previous research [15][16][17] to enable oneto-one comparisons.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations